dX/dt = (X-1)(1-2X); ln((2X-1)/(X-1) Verify that the indicated expression is an implicit solution of the given first-order differential equation.
Follow Math Help Forum on Facebook and Google+
$\displaystyle \frac{{dx}} {{dt}} = (x - 1)(1 - 2x) \iff \frac{1} {{(x - 1)(1 - 2x)}}\,dx = dt$ It's separable, can you take it from there?
no i dont understand where you are going with that and what the point was!!!
Originally Posted by karie no i dont understand where you are going with that and what the point was!!! Integrate both sides now.
View Tag Cloud